2016
DOI: 10.1111/adb.12464
|View full text |Cite
|
Sign up to set email alerts
|

Region specific activation of the AKT and mTORC1 pathway in response to excessive alcohol intake in rodents

Abstract: We previously reported that the kinase AKT is activated in the nucleus accumbens (NAc) of rodents in response to excessive consumption of alcohol. One of the important downstream targets of AKT is the mammalian Target Of Rapamycin in Complex 1 (mTORC1), which was also activated by alcohol intake. mTORC1 controls dendritic protein translation, and we showed that the mTORC1-dependent translational machinery is activated in the NAc in response to alcohol intake. Importantly, systemic or intra-NAc inhibition of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
73
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(82 citation statements)
references
References 47 publications
8
73
1
Order By: Relevance
“…To test for brain region specificity, we measured the level of the protein in the two other striatal regions, the dorsomedial striatum (DMS) and the dorsolateral striatum (DLS). In line with the observation that alcohol does not activate mTORC1 in the DMS and DLS (Laguesse et al, 2016), Prosapip1 levels were unaltered by alcohol in either striatal regions (Figures S2D and S2E). Together, these data suggest that the translation of Prosa-pip1 is selectively induced in the NAc in response to chronic intermittent consumption of high levels of alcohol.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…To test for brain region specificity, we measured the level of the protein in the two other striatal regions, the dorsomedial striatum (DMS) and the dorsolateral striatum (DLS). In line with the observation that alcohol does not activate mTORC1 in the DMS and DLS (Laguesse et al, 2016), Prosapip1 levels were unaltered by alcohol in either striatal regions (Figures S2D and S2E). Together, these data suggest that the translation of Prosa-pip1 is selectively induced in the NAc in response to chronic intermittent consumption of high levels of alcohol.…”
Section: Resultssupporting
confidence: 88%
“…Rapamycin did not alter the total mRNA levels of Prosapip1 in the presence or absence of alcohol (Figure S1B), indicating that alcohol induced an increase in Prosapip1 translation without a change at the transcriptional level. In addition, rapamycin, even at a high dose (40 mk/kg), did not alter the translation of Prosapip1 in water-only-consuming animals (Figure S1C), suggesting that long-term alcohol intake that activates mTORC1 in the NAc (Laguesse et al, 2016; Neasta et al, 2010) is a prerequisite for mTORC1-dependent translation of Prosapip1.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Specifically, we showed that acute systemic administration of alcohol as well as episodes of heavy alcohol drinking activates mTORC1 in the NAc shell of rodents (Laguesse et al . 2016; Neasta et al . ).…”
Section: Alcohol and Mtorc1 Signalingmentioning
confidence: 99%